TRADISI HAFLATUL IMTIHAN DI PESANTREN SEBAGAI SUMBER SPIRITUAL DAN SOSIO KULTURAL DI PONDOK PESANTREN AL- HAYYAN SUMENEP - Agus Kharir (Bayan lin-Naas : Jurnal Dakwah Islam, 2023)
AbstractÂ The tradition of haflatul imtihan in Islamic boarding schools can be used as a spiritual and socio-cultural source. Evidently the number of people who attended the event. There are performances that describe regional art sessions. Like a tambourine group performing songs or Islamic nasyid-nasyid of the Zipin dance which heeds the tambourine when it is played... this event can grow and develop their knowledge, faith, and piety. In this study there are two points that are focused on the history of the emergence of Haflatul Imtihan. And the function and existence of this Haflatul Imtihan. The research location in PP. Al-Hayyan Bandungan Karduluk Pragaan Sumnep, East Java. With this type of phenomenal descriptive qualitative research it produces the following: 1). The emergence of Haflatul Imtihan in PP. Al-Hayyan in 3 years after the establishment of the Al-Hayyan hut, namely in 1963. 2). In carrying out the Haflatul Imtihan event, careful preparation is needed both in terms of accommodation and funding. 3). The functions and benefits of the Haflatul Imtihan program are so that students are enthusiastic about learning, proving the distribution of knowledge achieved by distributing report cards. Tighten, increase the harmony of unity between communities, students, alumni sympathizers. 4). The Haflatul Imtihan Tradition as a spiritual source. It was proven that they came to the Haflatul Imtihan event in droves to witness the event being held at the Islamic Boarding School by preparing and wearing new clothes. There is a belief in the majority of the community that Haflatul Imtihan can increase the attractiveness of the community to attend school in Islamic boarding schools. Haflatul Imtihan at the top of the event was filled by lecturers who added knowledge, insight, faith, and improved morals.Â Keywords: Haflatul Imtihan, Spiritual, Socio-Cultural